2012
DOI: 10.1590/s0034-737x2012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Concentrações e composições químicas do meio nutritivo para o cultivo in vitro de orquídea

Abstract: Concentrações e composições químicas do meio nutritivo para o cultivo in vitro de orquídeaRev. Ceres, Viçosa, v. 59, n.1, p. 1-8, jan/fev, 2012 RESUMO ABSTRACT Chemical composition and component concentrations of culture medium for the in vitro growth of orchidOrchid seedlings grown in vitro respond differently to the different culture media used for this technique. This study compares the traditional Knudson (KC) medium used in orchid in vitro cultivation with a new medium formulation based on the KC medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…The use of different formulations of media, with the addition of mineral salts, hormones, vitamins or organic compounds, is aimed at improving the germination and the asymbiotic in vitro development of these seedlings (Martini et al 2001;Campos 2004;Rodrigues et al 2012). However, in vitro experiments have shown that symbiotic seed germination enables faster development than does germination in asymbiotic culture media (Markovina & McGee 2000;Takahashi et al 2001;Stewart & Kane 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of different formulations of media, with the addition of mineral salts, hormones, vitamins or organic compounds, is aimed at improving the germination and the asymbiotic in vitro development of these seedlings (Martini et al 2001;Campos 2004;Rodrigues et al 2012). However, in vitro experiments have shown that symbiotic seed germination enables faster development than does germination in asymbiotic culture media (Markovina & McGee 2000;Takahashi et al 2001;Stewart & Kane 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2ml were inoculated in the alternative culture media consisting of 30 g L -1 of commercial sugar, 2 g L -1 of fertilizer B & G  , 200 ml L -1 of coconut water, and 2 g L -1 of activated carbon. They were de-jellied with 4 g L -1 of Agar (Rodrigues et al, 2012) and the pH of the culture media was adjusted to 5.5 ± 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Em experimento anterior, doses de fertilizantes minerais compreendidas entre 0,25 e 2,25 g L -1 resultaram, para muitas variáveis de crescimento, em curvas lineares, não sendo possível definir a melhor dose de fertilizante a ser adicionada ao meio de cultivo (Rodrigues et al, 2012). Com base nesses resultados, foram estabelecidas as doses para este experimento.…”
Section: Resultsunclassified